1983
DOI: 10.1161/01.hyp.5.4.514
|View full text |Cite
|
Sign up to set email alerts
|

The conscious instrumented rabbit: a model for the study of mechanisms of blood pressure regulation during pregnancy.

Abstract: SUMMARY Conscious pregnant and nonpregnant rabbits were used to further evaluate the role of prostaglandin (PG) and plasma renin activity (PRA) in the systemic hemodynamics of pregnancy. Pregnant rabbits had high peripheral blood levels of both PGE 2 and PRA. Systemic blood pressure was not affected in either pregnant or nonpregnant by the administration of an inhibitor of prostaglandin synthesis. Pregnant rabbits, however, had a much larger decrease in blood pressure than nonpregnant animals when given the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Indomethacin may promote antikaliuresis indirectly, by inhibition of the renin-angiotensin aldosterone axis (37). The attenuated systemic pressor response to exogenous vasoconstrictors that develops during pregnancy has been observed in many species (26,(47)(48)(49)(50)(51)(52), present study). The mechanism(s) is not clearly defined, and prereceptor, receptor, and/or postreceptor phenomena could contribute.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Indomethacin may promote antikaliuresis indirectly, by inhibition of the renin-angiotensin aldosterone axis (37). The attenuated systemic pressor response to exogenous vasoconstrictors that develops during pregnancy has been observed in many species (26,(47)(48)(49)(50)(51)(52), present study). The mechanism(s) is not clearly defined, and prereceptor, receptor, and/or postreceptor phenomena could contribute.…”
Section: Discussionsupporting
confidence: 63%
“…Hart (65,66) has shown that aortic arterial and portal venous strips from pregnant rats display a reduction in barium-induced increments of tension. These studies (50,51,(64)(65)(66), including our own, perhaps suggest that pressor responsiveness in pregnant rabbits and rats are modified by different mechanisms.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Bay K 8644 (BAY), an L-VDCC agonist, was infused in pregnant and nonpregnant anesthetized rabbits (10,20,40, and 60 g/kg) and pregnant and nonpregnant conscious, chronically instrumented (conscious) rabbits (10,25, and 50 g/kg). BAY infusions resulted in greater elevation of mean arterial pressure in both anesthetized pregnant (n ϭ 6) vs. nonpregnant (n ϭ 6) (P Ͻ 0.05) and conscious pregnant (n ϭ 10) vs. nonpregnant (n ϭ 10) rabbits (P Ͻ 0.05).…”
mentioning
confidence: 99%